Assessment of posterior choanal obstruction caused by adenoidal hypertrophy: Intra-operative mirror versus rigid nasendoscopic examination. (July 2018) - Eweiss, Ahmed; Al Yaghchi, Chadwan; Sharma, Sunil; Wong, Phui Yee
Abstract: Objectives: The aim of the study is to compare the degree of posterior choanal obstruction caused by adenoidal hypertrophy intra-operatively, when assessed by mirror versus rigid nasendoscopic examination, in children undergoing adenoidectomy. Methods: This is a prospective blinded study including all consecutive paediatric cases undergoing adenoidectomy under care of the senior author during the period from June 2015 to December 2016. All cases were performed under general anaesthesia. The degree of posterior choanal obstruction caused by adenoidal hypertrophy was assessed in each patient using both a rigid nasendoscope and a nasopharyngeal mirror. Photographs of the choanae and the adenoids were obtained for both methods. Two independent ENT specialists (a registrar and a consultant), who were blinded to the clinical history and identity of the patients, assessed these photographs. Assessors scored the degree of choanal obstruction on the right and left sides separately out of 100%. The scores were analysed using the Two-Sample equal variance T-test function. Results: A total of 26 patients were included; all of them were children aged between 2 and 13 years. A total of 52 choanae were assessed and photographed, resulting in 52 photographs for the nasendoscopic views and 26 photographs for the mirror views. The trans-nasal nasendoscopic views consistently showed a significantly higher degree of posterior choanal obstruction compared to trans-oral mirror examination views (P-value < 0.001). There was no significant difference between the scores of both assessors (P-value > 0.05). In 8 of the 26 patients (30.7%), the registrar's decision would have changed from not proceeding with surgery had he only used the mirror view, to proceeding with surgery had he also used the nasoendoscopic view. This was the case for 6 of the 26 patients (23%) reviewed by the consultant. There were three patients in common in which both the registrar and the consultant would have similarly changed decisions. Conclusion: Intra-operative nasendoscopy is more sensitive than mirror examination in assessing the degree of posterior choanal obstruction due to adenoidal hypertrophy. It is important to consider nasendoscopy in patients with symptoms of adenoidal hypertrophy where mirror examination of the posterior choanae is negative.